Nilai-Nilai Puisi “Madura Akulah Darahmu” dalam Kajian Konseling Indigenous Masyarakat Pendalungan - Khairul Bariyyah; Alief Laili Budiyono; Yuana Kristiyorini; Nining Maizura (Jurnal Psikoedukasi dan Konseling)
Indigenous counseling offers an approach that counselors can utilize to address issues within the Pendalungan community. This counseling emphasizes the counselor's direct involvement in assisting clients by leveraging the clients' culture, values, or beliefs to achieve counseling goals. Counselors are also required to pay attention to the unique characteristics of the Pendalungan community.The local wisdom values employed are derived from the poem "Madura Akulah Darahmu". This local wisdom reflects the values of the Madurese community, known for their resilient character and determination to persevere until their goals are achieved. Therefore, the aim of this study is to explore the values in the poem "Madura Akulah Darahmu" as local wisdom in indigenous counseling.The study employs a literature review method. Results indicate that out of 50 reviewed articles, 9 were found relevant, demonstrating that the values in the poem "Madura Akulah Darahmu" can be applied in indigenous counseling to resolve issues in the Pendalungan community. Suggestions for future research include developing an indigenous counseling model incorporating the values of the poem "Madurah Akulah Darahmu".